2014
DOI: 10.1002/adsc.201400024
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐ and Silver‐Catalyzed [4+2] Cycloadditions of Ynamides with Oxetanes and Azetidines

Abstract: cycloadditions between ynamides and oxetanes are described; these reactions involve oxetanes and gold-p-ynamides as nucleophiles and electrophiles, respectively. Excellent cycloaddition regioselectivities are achieved over a reasonable range of ynamide and oxetane substrates. For azetidines, their [4+2] cycloadditions with ynamides are implemented more efficiently with silver hexafluoroantimonate, which is also compatible with various ynamides and azetidines. These two cycloadditions provide facile accesses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Alternatively, in the [3+2] cycloaddition, the benzylic cation 679 is obtained due to the stabilization effect of the 4-methoxyphenyl group. In a later study, they reported that oxetanes could also react with ynamides under the catalysis of gold­(I) to provide six-membered 6-amino-3,4-dohydro-2 H -pyrans …”
Section: Gold-catalyzed Reactions Of Epoxidesmentioning
confidence: 98%
See 1 more Smart Citation
“…Alternatively, in the [3+2] cycloaddition, the benzylic cation 679 is obtained due to the stabilization effect of the 4-methoxyphenyl group. In a later study, they reported that oxetanes could also react with ynamides under the catalysis of gold­(I) to provide six-membered 6-amino-3,4-dohydro-2 H -pyrans …”
Section: Gold-catalyzed Reactions Of Epoxidesmentioning
confidence: 98%
“…In a later study, they reported that oxetanes could also react with ynamides under the catalysis of gold(I) to provide six-membered 6-amino-3,4-dohydro-2Hpyrans. 168 In 2015, Balamurugan et al reported the Au(I)-catalyzed intermolecular reaction of aryl-and alkyl-substituted epoxides 680 and alkynes 681 in acetone (Scheme 107a). 169 More recently, Liu's group reported the synthesis of 1,4dioxepanes 692 in good yields through the Au(I)-catalyzed [4+3] annulation of t-butyl propiolate derivatives 690 with aryl and alkyl epoxides 691 (Scheme 108a).…”
Section: Gold-catalyzed Reactions Of Aryl Vinyl and Alkyl Aziridinesmentioning
confidence: 99%
“…In these two cycloaddition reactions, azetidines 331 and oxetanes 332 functioned as nucleophiles, whereas metal-p-ynamides functioned as electrophiles (Scheme 95). 244 Another [4+2] cycloaddition of push-pull 1,3-dien-5-ynes 335 and aldimines 336 or silyl aldimines 337 was described 245 This reaction could be mediated either by the catalytic amount of AgSbF 6 alone or by the AuClPEt 3 / AgSbF 6 bimetallic catalyst system, thereby allowing for the regioand diastereoselective formation of trans-5,6-dihydropyridin-2ones 338 and 339 in moderate yields. In contrast to push-pull 1,3-dien-5-ynes 335, the neutral, electron-deficient or electron-rich enynes did not result in dihydropyridones.…”
Section: Cycloadditionmentioning
confidence: 99%
“…This elegant transformation under mild conditions opened new avenues for gold(I)‐catalyzed (formal) cycloadditions of ynamides. Later on, the same authors reported gold(I)‐ and silver(I)‐catalyzed cycloadditions between ynamides 122 and oxetanes or azetidines, respectively [Scheme , Equations (2) and (3)] …”
Section: [4+2] Cycloadditions Of Ynamidesmentioning
confidence: 99%